Fungicide resistance status and chemical control options for the brassica pathogen Pyrenopeziza brassicae. (12th August 2021) - King, Kevin M.; Bucur, Diana E.; Ritchie, Faye; Hawkins, Nichola J.; Kaczmarek, Agata M.; Duan, Yabing; Kildea, Steven; West, Jonathan S.; Fraaije, Bart A.
Abstract: Pyrenopeziza brassicae causes leaf spot disease of Brassicaceae in Europe/Oceania (lineage 1) and North America (lineage 2). In Europe, fungicides currently used for disease management are sterol 14α‐demethylase ( CYP51 ) inhibitors (azoles), quinone outside inhibitors (QoIs), and succinate dehydrogenase inhibitors (SDHIs); methyl benzimidazole carbamates (MBCs) are no longer applied. In this study, in vitro screening revealed European populations (collected 2018–2020) had shifted towards decreased azole sensitivity, but the North American population (2014–2016) was highly sensitive. Genotyping revealed CYP51 substitutions G460S or S508T were prevalent in European populations, often with a CYP51 promoter insert. Compared to wildtype CYP51 isolates, those with G460S plus an insert (44/46/151/210/302 bp) were c.25–32‐fold and c.50‐fold less sensitive to tebuconazole and prochloraz, respectively; those with S508T plus an insert (44/46/151/233 bp) were c.9–15‐fold and c.25–40‐fold less sensitive to tebuconazole and prochloraz, respectively. Selection for G460S (quantified via pyrosequencing) under different fungicide regimes was investigated in UK field trials, but G460S levels were high (c.76%) before treatment, so further selection during the trials was unclear. Despite the high G460S frequency and low disease pressure, yield data indicated measurable benefit for both azole‐ and non‐azole‐based programmes. In vitro screening against the MBC carbendazim showed European populations were predominantly moderately resistant/resistant; the North American population was sensitive. European and North American populations were sensitive to QoI (pyraclostrobin) and SDHI (penthiopyrad) fungicides. Results support an azole plus QoI/SDHI mixing partner for robust disease control and decreased risk of resistance, with continued sensitivity monitoring to ensure optimal strategies are deployed. Abstract : European and North American populations of the fungus Pyrenopeziza brassicae (leaf spot of brassicas) were screened for possible differences in sensitivity to azole, MBC, QoI, and SDHI fungicides.